A Synthetic Route to Human Insulin Using Isoacyl Peptides1. Issue 15 (11th March 2014) - Liu, Fa; Luo, Ethan Y.; Flora, David B.; Mezo, Adam R.
Abstract The chemical synthesis of insulin has been a longstanding challenge, mainly because of the notorious hydrophobicity of the A chain and the complicated topology of this 51‐mer peptide hormone consisting of two chains and three disulfide bonds. Reported herein is a new synthetic route utilizing the isoacyl peptide approach to address the hydrophobicity problems. The incorporation of isoacyl dipeptide segments into both A and B chains greatly improved their preparation and purification, and the RP‐HPLC recovery of the chain ligation intermediates. The new route affords human insulin with a yield of 68 % based on the starting purified A chain and an overall yield of 24 % based on the substitution of the resin used for the preparation of A chain. To the best of our knowledge, this represents the most efficient route of human insulin chemical synthesis reported to date.